Níveis de engagement em enfermeiros da atenção primária à saúde - Silva, Albertina Gomes da (2018)
The engagement is a mental state of affective-cognitive achievement-positive motivational work-related, involving persistent sense of accomplishment, motivational and social in nature. Nurses with good levels of engagement will be more productive and can achieve greater resolution in the service to users of health services. Objective: To evaluate levels of engagement in nurses of primary health care units of municipality of São José do Rio Preto, São Paulo. Method: Cross-sectional study among nurses in primary health care units. Data collection were used two instruments: one prepared by the researchers, containing socio-demographic variables; and the Utrech Work Engagement Scale (UWES), composed of seventeen self-assessment items with three dimensions (force, dedication and absorption) and overall score. The calculation of scores of the dimensions of UWES proposed statistical model was used in Preliminary Manual UWES. Comparison of socio-demographic variables with the scores of the UWES occurred by the F test in analysis of variance (ANOVA), with a significance level of 95%. Results: 75 nurses participated, being 26 (34.7%) managers of units. There were female prevalence (94.7%), age between 29 and 39 years (52.0%), carry title of specialist (81.3%), married (57.3%), gazetted (68.0%), working 40 hours per week (98.7%), income six to 10 minimum wages (49.4%), acting on primary health care between three and 10 years (42.7%) satisfied with profession (92.0%), never thought of quitting profession (57.3%). The average scores of UWES ranged from 4.6 to 4.8 and engagement levels were high in all dimensions. Nurses who exercised the function of managers showed a very high level of Dedication (5.0; ± 1.4); professionals with 40 years or more showed very high levels in all dimensions [Dedication: 5.2 (± 0.9); Absorption: 5.0 (± 0.8); Force: 5.3 (± 0.8) and overall Score: 5.1 (± 0.8)]; professionals with over ten years of experience in the primary health care showed very high levels in all dimensions [Dedication: 5.0 (± 1.5); Absorption: 5.0 (± 1.5); Force: 5.0 (± 1.4) and overall Score: 5.0 (± 1.4)]. Conclusion: The study showed prevalence of female nurses, with less than 40 years old, married, with graduate course and satisfied with the work. Have formal link between three and 10 years of experience in the primary health care. The professionals showed high levels of engagement, which demonstrates that are excited and proud of activities engaged, energy and mood, concentration and effort, and persistence in adversity situations in environment laboral. The managers presented high involvement in carrying out its activities. The results show that primary health care system of municipality encourages engagement and ability to work of nurses, enhances the performance of team and promotes quality of care and effectiveness of assistance.